Benchmark of chromatin–protein interaction methods in haploid round spermatids - Wang, Ruolei; Wu, Yue; Zhou, Ze; Ma, Yicheng; Zhang, Weidong; Wang, Zihang; Luo, Weihan; Hua, Peng (Frontiers in Cell and Developmental Biology, 2025)
IntroductionChromatin–protein interactions are fundamental for regulation of gene transcription. While chromatin immunoprecipitation followed by deep sequencing (ChIP-seq) has long been the gold standard for mapping these interactions, emerging techniques such as CUT&RUN and CUT&Tag, which offer advantages such as low-input requirements and high signal-to-noise ratios, have aroused great attention. However, research addressing the potential biases introduced by enzyme-based tagmentation approaches and comparative assessment with ChIP-seq remain absent.MethodsThis study aims to systematically evaluate and compare the performance of ChIP-seq, CUT&Tag, and CUT&RUN for profiling genome-wide transcription factors and histone modification binding.ResultsOur analysis revealed that all three methods reliably detect histone modifications and transcription factor enrichment, with CUT&Tag standing out for its comparatively higher signal-to-noise ratio. Detailed peak comparison revealed unique and overlapping enrichment among the three techniques. Additionally, CUT&Tag can identify novel CTCF peaks compared with the other two methods. A strong correlation was observed between CUT&Tag signal intensity and chromatin accessibility, highlighting its ability to generate high-resolution signals in accessible regions.DiscussionThe systematic comparison summarizes the differences between CUT&Tag and CUT&RUN in terms of the signal-to-noise ratio and bias toward accessible chromatin. Considering the experimental procedures, signal specificity, and inherent biases, we recommend tailoring the choice of method to the type of chromatin–protein interaction under study. CUT&Tag offers a promising alternative for applications requiring high sensitivity and reduced background noise.